139 Bispecific Antibody-Redirected Immunotherapy of Her2/neu-expressing Uterine Cancer. (1st January 2006) - Anderson, E. M.; Hamilton, C. A.; Chan, J. K.; Karimi, M.; Baker, J.; Husain, A.; Teng, N. N.; Negrin, R. S.
Abstract : Purpose of Study: Cytokine-induced killer cells (CIKs) are ex vivo activated and expanded CD8 + natural killer T cells that have been shown to have cytotoxic activity against cancers in randomized clinical trials. We determined the cytotoxic activity of CIK cells against endometrioid and serous papillary (UPSC) uterine cancer cell lines and evaluated the ability of trastuzumab and Her2xCD3 bispecific antibodies to enhance CIK-mediated cytotoxicity in Her2/neu-expressing uterine cancer cells. Methods: CIKs were generated by activating donor T cells with interferon-gamma followed by stimulation with anti-CD3 monoclonal antibody and interleukin-2. CIKs were characterized using FACS analysis. Expression of Her2/neu on uterine cancer cell lines was demonstrated by immunofluorescence microscopy. The cytotoxicity of CIKs was quantified by 4-hour 51 Cr release assays against uterine cell lines HEC-1A (endometrioid) and SPEC-2 (UPSC). Bispecific antibodies against Her2/neu (BSAbHer2) were designed using chemical conjugation methods. Anti-NKG2D monoclonal antibodies were used in antibody blocking assays. Results: CIKs developed cytotoxic activity after 10 to 14 days of culture. Using FACS analysis, we found that the population of CD3 + CD8 + T cells increased from 24% to 56% over 21 days, while the CD3 + CD56 + T cells increased from 7% to 14%. Immunofluorescence microscopy revealed that both cell lines overexpressed Her2/neu. Cytotoxicity assays were performed at effector to target (E:T) ratios of 10:1, 20:1, 40:1, and 100:1 with increasing E:T ratio correlating directly with mean percent specific lysis. At the 100:1 E:T ratio, the mean percent lysis of CIKs against HEC-1A and SPEC-2 cells was 38.8% (± 0.21) and 35% (± 3.4), respectively. Trastuzumab did not affect the cytotoxic activity of CIKs. However, BSAbHer2 redirection significantly enhanced the cytotoxicity of CIKs against HEC-1A and SPEC-2 cells with a mean percent lysis of 66.3% (± 1.0) and 50% (± 2.7), respectively. Anti-NKG2D antibodies significantly reduced CIK activity by 49% and 47% in HEC-1A and SPEC-2 cells, respectively. Conclusion: CIK cells have cytotoxic activity both endometrioid and UPSC cell lines. Redirection by BSAbHer2 significantly increased CIK cell-mediated cytotoxicity against Her2/neu-expressing cell lines. The mechanism of CIK cytotoxicity appears to be partly mediated by the NKG2D receptor.